Perencanaan Keuangan Dan Manajemen Biaya Sebagai Upaya Peningkatan Pendapatan Pelaku Usaha Di Desa Timbang Jaya Kecamatan Bahorok Langkat Sumatera Utara - Irawan Irawan (University of Muhammadiyah Sumatera Utara, 2020)
Small and medium business actors Provide knowledge of partners in assessing accurate production costs and providing education in the field of promotion. Work procedures to support the realization of the solutions offered, then first make preliminary observations in the field by approaching them through interviews and finding problem phenomena. Finally, evaluate the results by re-observing community problems. The results of the implementation of this service, cost management, understanding of financial planning and cost management for small business actors in Timbang aya Village, Bahorok Langkat District, have experienced a fairly good increase. In addition, the results of this dedication can form the basis for conclusions in the field that financial planning and cost management can better influence income through an understanding of financial and cost aspects. The better the existing Financial Planning and Cost Management, the stronger the impact on the income of business actors